ANALISIS HUKUM PERATURAN PENERIMAAN PEGAWAI NEGERI SIPIL DI DAERAH MENURUT UNDANG-UNDANG NO. 43 TAHUN 1999 TENTANG POKOK-POKOK KEPEGAWAIAN (STUDI PENERIMAAN PNS DI PEMKO MEDAN) - Andi Nova Bukit; Budiman Ginting; Pendastaren Tarigan; Faisal Akbar Nasution (USU LAW JOURNAL, 2014)
Abstract Good governance principle should be a guidance for the government of Medan city in executing candidates for civil servant recruitment. In this research, there are several issues formulation to be discussed namely procedures of acceptance candidates for Civil Servants, procedure of acceptance candidates for Civil Servants in government of Medan city based on the principle of transparency and accountability, and acceptance of Civil Servants in creating good governance in government of Medan city. Procedure of acceptance candidates for Civil Servants in government of Medan city is performed by proposal of mayor, and objectively conducted in collaboration with universities conducted by the Civil Service Agency  and witnessed by the police and the inspectorate of Medan City. Procedure of acceptance candidates for Civil Servant in government of Medan city not been fully carried out the principle of transparency and accountability. Recruitment of civil servants in creating good governance is implemented in accordance with mechanism to be in force in the legislation and the government also sought to implement bureaucratic reforms to create clean governance and authoritative or known more as good governance ( good governance ) as inseparable part of the overall agenda of the government. Key word: Recruitment of Civil Servant